Witte de With - Cahier = 1, October 1993 : Mutti-Vati Kultur -Till Death do us part - As Long as it lasts. - Akkerman, Philip; Buchloh, Benjamin H.D.; Chamberlain, Patrick; Chevrier, Jean-François; Dercon, Chris; Gerdes, Ludger; Huttenlocher, Britta; Jacobs, Henri; Krauss, Rosalind E.; Pitz, Hermann; Van Snick, Philippe; Walravens, Daniel; et al. (Dusseldorf : Richter Verlag, 1993)
Akkerman, Philip ; Barney, Matthew ; Beuys, Joseph ; Birza, Rob ; Broodthaers, Marcel ; Bustamante, Jean-Marc ; Duchamp, Marcel ; Erice, Victor ; Ernst, Max ; Evans, Walker ; Gerdes, Ludger ; Giacometti, Alberto ; Graham, Dan ; Haagmans, Fons ; Hesse, Eva ; Huttenlocher, Britta ; Jacobs, Henri ; Kelley, Mike ; De Keyser, Raoul ; Lissitzky, El ; Mik, Aernout ; Mondriaan, Piet ; Pollock, Jackson ; Richter, Gerhard ; Schouten, Marien ; Van Snick, Philippe ; Stockholder, Jessica ; Wall, Jeff ; Walravens, Daniel ; Weiner, Lawrence
Engels & Nederlands & Frans
boek